(untitled) (LACCEI, 2024)
In this work, are presented a diagnosis of the situation of the traditional way and of the teaching methods in a Faculty of the Electromechanical Engineering career and a proposal to motivate students to solve problems associated with laboratory experiences or workshops, which mobilize the competencies in training from the perspective of teachers and students. One of the empirical experiences that reveals competencies in group approaches and focused on students is presented, generated by the need to solve a specific problem whose prototype they had to build.